Knowledge and perception about health risks of cigarette smoking among Iraqi smokers - Omar Thanoon Dawood; Mohammed Abd Ahmed Rashan; Mohamed Azmi Hassali; Fahad Saleem (Wolters Kluwer Medknow Publications, 2016)
Background: Smoking is a major public health problem, especially in Iraq. There is very little information had been documented regarding smoking risk factors and quit intention among Iraqi smokers. Objectives: The main objectives of this study are to determine smokers' knowledge and perception about smoking health risks; and to determine smoking behavior and quitting intentions among Iraqi smokers; as well as to predict the factors that may associate with quit intentions. Methods: A cross-sectional study was conducted at the outpatient clinic in Tikrit Teaching Hospital, Tikrit City, Iraq. Adult smokers who are smoking cigarette everyday and able to communicate with the researcher were invited to participate in the study. A self-administered questionnaire was used to collect data from 386 participants. Results: This study showed that smokers had low awareness about some risk effects of smoking such as lung cancer in nonsmokers (30.1%), impotence in male smokers (52.6%), premature ageing (64%), and stroke (66.3%). In addition, the high score of knowledge and perception was significantly associated with quitting intention. Conclusion: Smokers' knowledge and perception regarding smoking health effects were low, especially in terms of secondhand smokers. Many efforts needed from health policy-makers and health care professionals to disseminate information about the risks of smoking and health benefits of give up smoking.